Building Sustainable Villages: The Kembang Desa Approach to BKP-MBKM Implementation - Rachmaningsih, Emy Kholifah; Rahayu, Yeni Dwi; Wardhana, Danu Indra (Universitas Padjadjaran, 2024)
This study aims to describe the implementation of 'Kembang Desa' as a tourism village development model. This study uses a qualitative descriptive research method. The results of the study are the village development needs to be accelerated by increasing the use of natural potential, community potential, social institutional potential and local economic potential and local culture, as well as the potential of government officials to support the development of tourist villages. Local wisdoms of the community can be social capital for the development of tourist villages. This great potential needs to be developed through the alignment of innovative government policies by developing cooperation with various parties, including universities. Partnerships with Universities can be realized through the implementation of the Village Development BKP-MBKM. ‘Kembang Desa’ Model has succeeded in realizing university advocacy on the development of Kemiri Tourism Village. The implication of this research for the development of science is to strengthen understanding of the importance of collaboration between government, community and universities in exploiting local potential for developing tourist villages, while for improving managerial practice it is to provide guidance on how to implement the 'Village Development' model by involving various parties. innovatively to accelerate the development of tourist villages.